Regional environmental change versus local signal preservation in Holocene thermokarst lake sediments: a case study from Herschel Island, Yukon (Canada) - Fritz, Michael; Unkel, Ingmar; Lenz, Josefine; Gajewski, Konrad; Frenzel, Peter; Paquette, Nathalie; Lantuit, Hugues; Körte, Lisa; Wetterich, Sebastian (Journal of paleolimnology, 2015)
Thermokarst lakes cover nearly one fourth of ice-rich permafrost lowlands in the Arctic. Sediments from an athalassic subsaline thermokarst lake on Herschel Island (69°36′N; 139°04′W, Canadian Arctic) were used to understand regional changes in climate and in sediment transport, hydrology, nutrient availability and permafrost disturbance. The sediment record spans the last ~ 11,700 years and the basal date is in good agreement with the Holocene onset of thermokarst initiation in the region. Electrical conductivity in pore water continuously decreases, thus indicating desalinization and continuous increase of lake size and water level. The inc/coh ratio of XRF scans provides a high-resolution organic-carbon proxy which correlates with TOC measurements. XRF-derived Mn/Fe ratios indicate aerobic versus anaerobic conditions which moderate the preservation potential of organic matter in lake sediments. The coexistence of marine, brackish and freshwater ostracods and foraminifera is explained by (1) oligohaline to mesohaline water chemistry of the past lake and (2) redeposition of Pleistocene specimens found within upthrusted marine sediments around the lake. Episodes of catchment disturbance are identified when calcareous fossils and allochthonous material were transported into the lake by thermokarst processes such as active-layer detachments, slumping and erosion of ice-rich shores. The pollen record does not show major variations and the pollen-based climate record does not match well with other summer air temperature reconstructions from this region. Local vegetation patterns in small catchments are strongly linked to morphology and sub-surface permafrost conditions rather than to climate. Multidisciplinary studies can identify the onset and life cycle of thermokarst lakes as they play a crucial role in Arctic freshwater ecosystems and in the global carbon cycle of the past, present and future.
Gesehen am 19.02.2025